(untitled) (Journal of Technology and Operations Management, 2025)
Theoretically, operations management (OM) is concerned with the designing and controlling processes or redesigning business operations for production of goods and services. More so in managing oil spills from tankers in the Straits of Malacca (SOM). Mistakes in decision making couple with outdated practices exposed marine living and non-living resources to damages as a result of the shipping casualties. In any major global oil pollution from tankers or sometimes addresses as oil pollution disaster has hardly achieved a fully oils recovery due to several factors; natural or physical or both. In the case, the previous study found that this phenomenon happened anywhere in the world including in the SOM. Operations management of this specialised mechanism requires specialists from various expertise such as engineering, chemical, biological, nautical, environmental economics, legal persons and social scientists. The whole spectrum of expertise determined the structure of frameworks such as legislation, institutional and operational that assimilated into national oil spill contingency plan (NOSCP). The plan documentation dictated the requirement of oil spills preparedness and response, distribution of oil spill response equipment (OSRE) stockpile strategically, and the way how its operations be managed and maintained to undertake any eventuality of future oil spills disaster in the SOM.